Language, Culture and Local Government Administration in Nigeria - Adegbite, Wale (2014)
This study describes the role of language as an agent of effective communication in local government affairs in Nigeria. First, the paper establishes the relationship between language and culture and describes language as the most vital but neglected tool for cultural development. Second, with a conception of the local government as a cultural, albeit politico-cultural institution in the Nigerian nation, the paper then describes the patterns of language choice for communication in local government affairs in Nigeria. The paper specifies the domains of language use in local government affairs in Nigeria and observes the patterns and problems of language choice for effective communication in these domains. Then adopting some principles of bilingualism-biculturalism as a theoretical base, the paper suggests ways of promoting efficient language choices in order to enhance efficient local government administration. The paper suggests that for external communication the English language should be used for local-local, local-state and local-federal intergovernmental interactions. However, at the internal level, the indigenous language(s) should be used for official and public functions, while the room is also created for alternation between languages in cosmopolitan areas. Furthermore, interpretation and translation are useful interlingua facilities that can enhance the projection and modernization of languages in external communication and also in cosmopolitan internal communication. From the bilingual-bicultural perspective, it is observed that both the indigenous and second languages have vital roles to play in the evolvement of cultural identity at the local government level in Nigeria. However, the primacy of mother tongues must be recognized.